(untitled) (Global Journal of Medical Research, 2015)
In our study we synthesized schiff’ base of sulphadiazine on treating with aromatic aldehydes like para diethyl amino benzyldehyde and paradimethyl amino benzyldehyde. The synthesized schiff’s bases were converted to its cationic amphiphilic bases by treating with methyl iodide. The cationic schiff bases were converted to metal complexes by treating with metals like copper chloride (CuCl2), zinc chloride (ZnCl2) and cadmium chloride (CdCl2). All the synthesized compounds were characterized by elemental analysis, IR and H1 NMR. Synthesized compounds were screened for anti-inflammatory and antidepressant activity. Copper metal complexes showed excellent anti-inflammatory activity and zinc metal complexes showed excellent anti-depressant activity.